Free Peroneal Artery Perforator-Based Flap for Soft Tissue Reconstruction of the Finger - Kawamura, Kenji; Yajima, Hiroshi; Omokawa, Shohei; Shimizu, Takamasa; Hayashi, Satoshi; Maegawa, Naoki; Nakanishi, Yasuaki; Kira, Tsutomu; Onishi, Tadanobu; Hayami, Naoki; Hasegawa, Hideo; Tanaka, Yasuhito (Journal of Reconstructive Microsurgery Open, 2017)
Background The peroneal artery perforator-based flap has been widely used as a pedicled propeller flap for soft tissue reconstruction in the lower extremity; however, its application as a free flap has been rarely reported. We report on the utility of the free peroneal artery perforator-based flap for finger soft tissue reconstruction.Methods Twelve patients underwent reconstructions of soft tissue defects of the finger with free peroneal artery perforator-based flaps. The soft tissue defects were located either dorsally and/or laterally on the fingers. The size of the flaps ranged from 5 × 2 to 8 × 3 cm. The length of the vascular pedicles ranged from 4 to 5 cm. The artery and vein of the perforator vessels were anastomosed in the finger to the digital artery and subcutaneous vein, respectively.Results All twelve flaps survived completely, and the donor site in the lower leg was closed primarily in all cases. Secondary defatting was performed in six cases, while in the remaining cases, thinning of the flap was performed when the flap was transferred.Conclusion The advantages of the free peroneal artery perforator-based flap for finger soft tissue reconstruction include the following: the flap is flexible and can be thinned to match the texture of the finger; elevation of the flap is easy; the donor site can be closed primarily; there is no need to sacrifice any main arteries in the lower leg; and the diameter of the perforator vessels is suitable for anastomosis to the digital artery and subcutaneous vein in the finger.
Keywords: perforator flap; peroneal artery perforator-based flap; finger reconstruction